2013
DOI: 10.3171/2013.4.jns122195
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife surgery for large vestibular schwannomas: a single-center retrospective case-matched comparison assessing the effect of lesion size

Abstract: Object. Gamma Knife surgery (GKS) is a safe and effective treatment for patients with small to moderately sized vestibular schwannomas (VSs). Reports of stereotactic radiosurgery for large VSs have demonstrated worse tumor control and preservation of neurological function. The authors endeavored to assess the effect of size of VSs treated using GKS.Methods. This study was a retrospective comparison of 24 patients with large VSs (> 3 cm in maximum diameter) treated with GKS compared with 49 small VSs (≤ 3 cm) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Although radiosurgery has been reported to produce similar facial nerve outcomes for Koos grade 3 tumors (mean volume 9 cm 3 ), its role in the context of large vestibular schwannomas remains controversial and it may be indicated only in patients with minimal symptoms of brainstem compression, surgical contraindications, or significant residual tumor mass despite attempted debulking. 4,15,25,41,43,44,47,50 A proposal to stage large vestibular schwannomas between 2 surgeries has been shown to improve facial nerve outcome and morbidity. 30 Staging the tumor resection was decided intraoperatively if there was cerebellar or The extent of resection is another important factor, with several studies demonstrating significantly lower rates of recurrence with complete or near-complete resections compared with subtotal or partial debulking.…”
Section: Discussionmentioning
confidence: 99%
“…Although radiosurgery has been reported to produce similar facial nerve outcomes for Koos grade 3 tumors (mean volume 9 cm 3 ), its role in the context of large vestibular schwannomas remains controversial and it may be indicated only in patients with minimal symptoms of brainstem compression, surgical contraindications, or significant residual tumor mass despite attempted debulking. 4,15,25,41,43,44,47,50 A proposal to stage large vestibular schwannomas between 2 surgeries has been shown to improve facial nerve outcome and morbidity. 30 Staging the tumor resection was decided intraoperatively if there was cerebellar or The extent of resection is another important factor, with several studies demonstrating significantly lower rates of recurrence with complete or near-complete resections compared with subtotal or partial debulking.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,16,19,27 Despite variations in technologies, fractionation, delivery techniques, dose delivered, conformality of 3D dose delivery, and selectivity (fall off outside the tumor volume), focused radiation has become an important management option across the world. Previous studies demonstrated that despite variations in methods and technologies, sustained tumor growth control was obtained in 90%-98% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…37 Compilation of the relevant literatures on the outcome of VS of at least Koos Grade III treated by radiosurgery, the overall progression free survival rates range from 82-100% at long-term follow-up (Table 4). 12,29,30,33,[37][38][39][40][41] The available evidence suggested that large VSs are potentially amenable to primary SRS therapy, but there may still be poor tumor control in the largest of tumors. We confirmed this relationship when further stratifying our cohort by volume, with tumors < 15 cm 3 associating with better control rates.…”
Section: Tumor Control: Radiosurgery As An Optionmentioning
confidence: 98%
“…Prior work has similarly indicated that cystic pathology is not predictive of tumor progression, collectively suggesting that SRS treatment for large cystic lesions focus on postoperative complication management. 33,38 While prior work has shown that preoperative hydrocephalus is more common for cystic VS of all sizes, few articles have specifically characterized the full relationships across large, cystic VS, and their need for postoperative shunting. 43,44 Williams et al reported that there was a tendency for large tumors to present with cystic lesions (25% vs 0%), hydrocephalus (8% vs 0%) and require a postoperative shunt (8% vs 0%) relative to smaller VSs, but did not specify their interaction.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation